Energy conservation for refrigeration systems by means of hybrid fuzzy adaptive control techniques (2016)
Most vapour compression refrigeration systems still operate under on–off control, although it is well known that the application of any other control method could result in improved COP. For that purpose, the present paper experimentally studies the use of adaptive fuzzy hybrid control and design of experiments techniques, as well as the application of the response surface methodology, in a 5-ton vapour compression system with a variable speed compressor and an electronic expansion valve. Evaporation temperature and evaporator overall conductance were found to be the most relevant input parameters to the fuzzy hybrid control system, where the optimal trajectory was sought without taking into account the elapsed time. Results have shown that the knowledge of the most relevant parameter of the system allowed for the control system to seek high COP zones. It has been found that this type of technique does not jeopardize the control performance, which remains robust.